Physico-Chemical Characteristics and Fatty acid Profiles of Smoked Skipjack Tuna (Katsuwonus pelamis) Using Coconut Fiber and nutmeg Shell Smoking materials - Netty Salindeho (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Skipjack tuna is one of the most popular fish processed through a traditional smoking method in North Sulawesi. This study was aimed to analyze the physicochemical characteristics and fatty acid profiles of skipjack tuna, Katsuwonus pelamis, smoked using coconut fibers and nutmeg shell for 15 hours of smoking. Results found that the smoked skipjack using the nutmeg shell smoking material had the lower watercontent and aw, and higher protein, fat and ash content than those smoked with coconut fiber (P<0.05). The fatty acid profile of the smoked skipjack using nutmeg shell showed lower total Saturated Fatty Acid(SFA) and higher Monounsaturated Fatty Acid (MUFA) and Polyunsaturated Fatty Acid (PUFA) than those smoked with coconut fiber (P<0.05). The organoleptic test showed for smoking materials of coconut fiber and nutmeg shell, respectively,  as follows: color was 4.97±1.32 and 5.87±0.89; taste was 5.64±0.99 and 5.80±0.88; the texture was 5.17±1.17 and 5.64±1.21; and aroma was 5.67±0.88 and 5.90±0.85. The panelists can accept the smoked skipjack using both smoking materials of coconut fiber and nutmeg shell.